GAMBARAN KLINIS SEPSIS DAN KADAR NITRIC OXIDE PADA MENCIT YANG DIIMBAS DENGAN LIPOPOLYSACCHARIDE - Sotianingsih Sotianingsih; Soeharyo Soeharyo; Lisyani S; Guntur H (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2013)
Sepsis remains a health problem because of the high related mortality and morbidity. One of the efforts is the improvement of knowledgeabout manifestation and pathophysiology of sepsis at the level of molecular biology. Nitric oxide (NO) levels increased in sepsis and this isrelated to the occurrence of cell apoptosis. The purpose of this study was to know and to see the clinical picture of sepsis and elevated levels ofNO in mice Balb/C which were injected with lipopolysaccharide (LPS). In this research, the mice were divided into three (3) groups, groupA were injected with saline, group B were injected with LPS 0.1 mg per mouse, while group C was injected with 0.2 mg per mouse. Themice were then measured by clinical parameters from day 0 and day 1, and 3,5 to 7. The levels of NO were assessed by blood sampling asmuch as 1 cc from the peri orbital plexus and examined by Griess method on days 1, 3, 5, 7. The results of the study showed that from theweight parameter there was a decrease in body weight on day 1 in group B and C and the weight continued to decline until day 3. From thetemperature parameter it was shown that the temperature decreased both in group B and C on day 1 but on day 3 and so on varies in bothgroups. From the piloerection parameters from day 1 to day 7 showed that there was piloerection in both groups. Related to the discharge byperi orbital parameters and diarrhoea many variations, occurred on day 1 peri orbital discharge and diarrhoea was found, but not uniformlyin all the mice in each group. On day 5 and 7 the peri orbital discharge and diarrhoea were not visible. NO levels increased mainly on day3 and the percentage was higher in group C and on day 5 and day 7 the levels were negative. In conclusion in this study it was shown, thatthe clinical picture is striking, weight loss and increased levels of NO occurs on day 3 of the observation.